The beneficial effect of parasympathetic reactivation on sympathetic drive during simulated rugby sevens - Douglas, J.; Plews, D. J.; Handcock, P. J.; Rehrer, N. J. (International Journal of Sports Physiology and Performance, 2016)
Purpose: To determine whether a facilitated recovery via cold-water immersion (CWI) after simulated rugby sevens would influence parasympathetic reactivation and repeated-sprint (RS) performance across 6 matches in a 2-d tournament.